Modern physics - Serway, Raymond A.; Moyer, Curt A.; Moses, Clement J. (Cengage, 2005)
Summary: Provides an introduction to relativity, quantum mechanics, and statistical physics as well as applications of these theories to molecular physics, condensed matter physics, nuclear physics, particle physics, and cosmology.